Venom proteomes of South and North American opisthoglyphous (Colubridae and Dipsadidae) snake species: A preliminary approach to understanding their biological roles - Peichoto, María Elisa (2012)
Opisthoglyphous snake venoms remain under-explored despite being promising sources for ecological, evolutionary and biomedical/biotechnological research. Herein, we compared the protein composition and enzymatic properties of the venoms of Philodryas baroni (PbV), Philodryas olfersii olfersii (PooV) and Philodryas patagoniensis (PpV) from South America, and Hypsiglena torquata texana (HttV) and Trimorphodon biscutatus lambda (TblV) from North America. All venoms degraded azocasein, and this metalloproteinase activity was significantly inhibited by EDTA. PooV exhibited the highest level of catalytic activity towards synthetic substrates for serine proteinases. All venoms hydrolyzed acetylthiocholine at low levels, and only TblV showed phospholipase A2 activity. 1D and 2D SDS-PAGE profile comparisons demonstrated species-specific components as well as several shared components. Size exclusion chromatograms from the three Philodryas venoms and HttV were similar, but TblV showed a notably different pattern. MALDI-TOF MS of crude venoms revealed as many as 49 distinct protein masses, assigned to six protein families. MALDI-TOF/TOF MS analysis of tryptic peptides confirmed the presence of cysteine-rich secretory proteins in all venoms, as well as a phospholipase A2 and a three-finger toxin in TblV. Broad patterns of protein composition appear to follow phylogenetic lines, with finer scale variation likely influenced by ecological factors such as diet and habitat.